2019
DOI: 10.1186/s13054-018-2305-5
|View full text |Cite
|
Sign up to set email alerts
|

TCR activation mimics CD127lowPD-1high phenotype and functional alterations of T lymphocytes from septic shock patients

Abstract: Background Sepsis is the leading cause of mortality for critically ill patients worldwide. Patients develop T lymphocyte dysfunctions leading to T-cell exhaustion associated with increased risk of death. As interleukin-7 (IL-7) is currently tested in clinical trials to reverse these dysfunctions, it is important to evaluate the expression of its specific CD127 receptor on the T-cell surface of patients with septic shock. Moreover, the CD127 low PD-1 high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Although the clinical scores, such as APACHE II [25], SOFA [26] and the PaO 2 /FiO 2 ratio [27], have been widely used to predict the results of clinical practice patients of ARDS. We further found that the lymphocyte/ neutrophil ratio AUC was higher than the PaO 2 /FiO 2 ratio, BMI, APACHE II score, and SOFA score alone in predicting 100-day survival in ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical scores, such as APACHE II [25], SOFA [26] and the PaO 2 /FiO 2 ratio [27], have been widely used to predict the results of clinical practice patients of ARDS. We further found that the lymphocyte/ neutrophil ratio AUC was higher than the PaO 2 /FiO 2 ratio, BMI, APACHE II score, and SOFA score alone in predicting 100-day survival in ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical scores, such as APACHE II [26], SOFA [27] and the PaO 2 /FiO 2 ratio [28], have been widely used in clinical practice to predict outcome in ARDS patients, we further found that the lymphocyte/neutrophil ratio AUC for predicting 100-day survival in ARDS patients was higher than that for the PaO 2 /FiO 2 ratio, BMI, APACHE II score, and SOFA score alone. The lymphocyte/neutrophil ratio in combination with the lymphocyte count slightly increased the AUC for predicting 100-day survival, yet there was no difference compared with the lymphocyte/neutrophil ratio alone.…”
Section: Discussionmentioning
confidence: 59%
“…T cell receptor activation would affect the occurrence of T-cell population and the development of T-cell alterations in septic shock. 30 Therefore, it can be concluded that HSBD might exert its therapeutic effects on severe COVID-19 by inhibiting the pathogens-induced inflammatory response and regulating the immune function of T cells. This conclusion was consistent with the results of GO_BiologicalProcess enrichment.…”
Section: Discussionmentioning
confidence: 99%